2021
DOI: 10.18203/2349-3933.ijam20212867
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with blood pressure in end stage renal disease patients receiving regular hemodialysis at Wangaya general hospital, Denpasar

Abstract: Background: Hypertension is common findings in end-stage renal disease (ESRD) patients receiving hemodialysis, around two third among them are poorly controlled. We analyzed factors affecting blood pressure in patients undergoing regular hemodialysis.Methods:A single center cross-sectional study conducted including 65 patients receiving regular hemodialysis at hemodialysis unit Wangaya general hospital, Bali, Indonesia. Ordinal regression test was performed to analyze the relationship between factor associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A cross sectional study and an observational retrospective concluded that gender was not related to uncontrolled blood pressure in regular hemodialysis patients (p = 0.878 and p = 0.83). 6,14 There was also no significant difference between the controlled and uncontrolled blood pressure groups in hemodialysis patients. 9 However, the findings of these studies did not concur with the cross-sectional study of Amr et al 7 which concluded that gender was significantly associated with blood pressure (p = 0.002).…”
Section: Sosio-demographicmentioning
confidence: 85%
See 4 more Smart Citations
“…A cross sectional study and an observational retrospective concluded that gender was not related to uncontrolled blood pressure in regular hemodialysis patients (p = 0.878 and p = 0.83). 6,14 There was also no significant difference between the controlled and uncontrolled blood pressure groups in hemodialysis patients. 9 However, the findings of these studies did not concur with the cross-sectional study of Amr et al 7 which concluded that gender was significantly associated with blood pressure (p = 0.002).…”
Section: Sosio-demographicmentioning
confidence: 85%
“…A total of 175 articles were identified through database searches, comprising 27 from PubMed, 30 from Scopus and 118 from Google Scholar. Furthermore, a total of 160 articles were excluded for various reasons, including duplicates (6), irrelevant (24), non-dialysis (58), not original research (24), case reports (44), and post-renal transplantation (4). Therefore, the full-text articles assessed for eligibility was 15 (FIGURE 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations